Effect of barrel to barrel variability on colour and phenolic composition of a red wine from Douro PDO - Pfahl, Leonard Maximilian (2020)
Vinifera Euromaster - European Master inViticulture and Oenology Engineering / Instituto Superior de Agronomia. Universidade de Lisboa / Institut National d' Études Superieurs Agronomiques de Montpellier